KESULITAN MENULIS AKSARA JAWA PADA SISWA KELAS 5 SD AL ISLAM PENGKOL JEPARA - Anjani, Falihatin; Wiranti, Dwiana Asih (Universitas Wahid Hasyim Semarang, 2024)
The reason for author addresses the issue of difficulty in writing Javanese script is that writing Javanese script is not as easy as writing alphabet. Therefore, the author wants to understand the factors causing and the forms of difficulties that students experience when writing Javanese script, as the Bahasa Jawa subject is very important for preserving Javanese culture so that it does not disappear. This research aims to analyze the forms of difficulty in writing Javanese script and their underlying causes. The difficulties in writing Javanese script include the students' struggle to differentiate between relatively similar Javanese script characters and the difficulty in memorizing Javanese script letters. The underlying causes are the limited teaching methods used by educators, which mainly rely on lectures, the lack of practice in writing Javanese script, and the decline in students' motivation to learn because they perceive it as a difficult subject to understand. This research uses a qualitative method; descriptive qualitative research is a study where data is obtained through analytical examination of each issue to be processed into narrative and oral data from the observed subjects. Descriptive qualitative data is obtained from questionnaires, interviews, and observations.